Autonomy and the genetics of behaviour - Mordini, Emilio (SMAD Revista Eletrônica Saúde Mental Álcool e Drogas (Edição em Português), 2006)
The idea that behaviour, personality traits, preferences and choices may be the result of a sort of biological decision-making programme, shaped by evolution and carried by DNA, conflicts with the idea of "autonomy". Indeed the term "autonomy" involves the idea of freedom and the capacity to be self-determining, to be in control of one's own life, beyond any influence of biological, psychological and social compulsive forces, genes included. Policy of scientific action has to be based both on a moment of universality, which is represented by determinism, and on the pragmatic demands posed by indeterminism and autonomy. Sometimes, scientists do not seem to realise this.